식사형태와 식사능력에 따른 요양병원 여자 노인 환자의 영양섭취조사 - 안혜진(Hye Jin Ahn); 강주희(Ju Hee Kang); 이홍미(Hong Mie Lee) (Korean journal of community nutrition, 2014)
Objectives: This study was carried out to determine nutritional status of elderly patients in a long-term care hospital according to meal type and eating ability. Methods: Subjects were 47 female patients aged over 65 ($79.3{±}7.1$ years) who resided in a long-term care hospital in Seoul. Thirty seven patients who ate diet orally were grouped according to meal type (27 general diet and 10 soft diet) and eating ability (26 eating by oneself and 11 eaten with help) and 10 were on tube feeding. Nutritional status was determined by food consumption and mid-arm circumference. Results: The mean adequacy ratios (MARs) of 12 nutrients (protein, calcium, phosphorus, zinc, vitamin A, vitamin $B_1$, vitamin $B_2$, vitamin $B_6$, niacin, folic acid, vitamin C) were 0.687 for general diet, 0.565 for soft diet, 0.680 for eating by oneself and 0.677 for eaten with help, which were significantly lower than 0.982 for tube feeding (p < 0.05 or p < 0.01). The patients on tube feeding had significantly lower % arm circumference compared to those who ate general diet (84.0% vs. 95.4%, respectively, p < 0.05). Nutrients intakes, nutrient adequacy ratio (NAR) and index of nutritional quality (INQ) were not different between meal types as well as eating ability. The most insufficiently consumed nutrients by the patients on diet were folic acid, vitamin $B_2$, and calcium (NAR 0.334~0.453, 0.515~ 0.539, and 0.516~0.533, respectively). Conclusions: The results suggested that regardless of meal type or eating ability, the subjects who were on diets in this study might have inadequate intake of folic acid as well as vitamin $B_2$, and calcium, which need to be reflected on menu planning. The measurement of mid-arm circumference presented more risk of malnutrition of patients on tube feeding than those on diets, despite apparently better nutrient consumption.